Teachers’ Competence, Classroom Environment, Learning Style of Students: A Structural Model on Mathematical Ability - Osic, Mervin Amba (International Journal on Emerging Mathematics Education, 2022)
The study was conducted to develop the best fit model of mathematical ability.  Specifically, it established the relationship among teachers’ competence, classroom environment, learning styles, and mathematical ability. Descriptive, correlational and causal comparative designs were utilized in this study.  The data were gathered from senior high school students. Moreover, sets of adopted survey questionnaires were used as instruments to obtain information from the participants. Mean, Pearson product moment correlation, multiple regression analysis and structural equation modeling were the statistical tool used.  The findings revealed that reflector and activist learner and role of students/peers found to be significant predictors of mathematical ability.  The best fit model of mathematical ability is best predicted by their learning styles and the classroom environment. The model suggests that that the more structured the learning style coupled with a conducive classroom environment the better the mathematical ability of the students.